Análisis de las condiciones operativas del tanque vertical pr-001 de capacidad nominal de 500 barriles para almacenamiento de diésel ubicado en la parroquia 7 de Julio cantón Shushufindi - Quilumba Ruiz , María Valeria (2023)
Storage tanks are commonly used in industries to store crude oil and its derivatives, in this case as the PR-001 diesel storage tank. This type of tank requires periodic inspections at different time intervals, in order to be able to analyze the settlement, roundness, and verticality, it is said that abnormalities may occur due to its long-term use. To ensure the trustworthiness of the structure, it is necessary to carry out periodic monitoring, develop a reliable and cost-effective monitoring style. Said monitoring consisted of taking topographic factors of the tank using the total station, this task was was done based on external observation and evaluation in the criteria of the API 653 standard, which indicates factors for the inspection, repair, alteration and reconstruction of tanks. So this investigation will show the results obtained from the calculations processed through the data provided by the area inspector.